ANALYSIS OF SUPPLIER SELECTION CRITERIA USING FUZZY AHP IN TEXTILE INDUSTRY IN INDONESIA - Lim Sanny; Yuliana Yuliana (Bina Nusantara University, 2018)
The purposes of this study are to determine the order of criteria and sub-criteria in supplier selection process by measuring the weight of each criteria and sub-criteria to find out the best supplier in each TPT industry sector for the company which become the subject of this study. The technique of collecting data is through questionnaire distribution to 5 respondents who are the experts of the company. The collected data were analysed using Fuzzy AHP approach. The result of this research will assist in giving beneficial solutions in decision making, especially in selecting the best suppliers based on supplier selection criteria and sub-criteria to supports an excellent supply chain management.